2018
DOI: 10.18176/jiaci.0192
|View full text |Cite
|
Sign up to set email alerts
|

Latest Insights on Food Protein–Induced Enterocolitis Syndrome: An Emerging Medical Condition

Abstract: Food protein-induced enterocolitis syndrome (FPIES) is a type of non-IgE-mediated gastrointestinal food hypersensitivity characterized by profuse vomiting that is frequently associated with pallor or/and lethargy and appears within 1 to 3 hours after ingestion of the offending food. A less frequent chronic form of FPIES is characterized by protracted vomiting, diarrhea, or both accompanied by poor growth. Although FPIES is considered a rare allergic disorder, increasing reports in recent years point to a real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
2
9
0
1
Order By: Relevance
“…It is worth discussing separately our results related to FPIES, due to its unique characteristics. Although FPIES is defined as a rare disease, 26,27 in our study population, 7.7% of children were affected by FPIES. Although literature suggested that FPIES is prevalent in males, 28 our cohort was almost equally composed by males (51.9%) and females (48.1%).…”
Section: Discussionmentioning
confidence: 72%
“…It is worth discussing separately our results related to FPIES, due to its unique characteristics. Although FPIES is defined as a rare disease, 26,27 in our study population, 7.7% of children were affected by FPIES. Although literature suggested that FPIES is prevalent in males, 28 our cohort was almost equally composed by males (51.9%) and females (48.1%).…”
Section: Discussionmentioning
confidence: 72%
“…If no acute symptoms occurred, patients were discharged home after 4 h of observation. Finally, in 2017, Vazquez-Ortiz et al [7] administered 0.3 g/kg of the food protein (3 g as maximal dose) divided into 3 equal doses given at 90-min intervals if no reaction occurred and, in 2018, Vila Sexto [4] administered the full serving size per age divided into 5 equal doses given every 20 min followed by 4 h of observation.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, an OFC should be considered between 18 and 24 months from the last FPIES episode to determine tolerance. 6 Most children will have resolution of their FPIES between the ages of 3 and 5 years. The age that tolerance develops to an offending food item depends on the food item in question, population, and severity of initial reaction.…”
Section: Discussionmentioning
confidence: 99%